Lexical Means of Intensification in the Story of Edgard Allan Poe (Eurasian Research Bulletin, 2022)
This article gives definition on the category of intensification and ways of its expressions. Moreover, it deals with means of the intensification and semantic characteristics of intensifying adjectives based on the story of Edgard Allan Poe.